Cooperation, Framing and Political Attitudes - Toke R. Fosgaard; Lars G. Hansen; Erik Wengström (Lund University, School of Economics and Management, Department of Economics, 2017)
This paper shows that political attitudes are linked to cooperative behavior in an incentivized experiment with a large sample randomly drawn from the Danish population. However, this relationship depends on the way the experiment is framed. In the standard game in which subjects give to a public good, contributions are the same regardless of political attitudes. In an economically equivalent version, in which subjects take from a public good, left-wingers cooperate significantly more than subjects in the middle or to the right of the political spectrum. Through simulation techniques we find that this difference in the framing effect across political point of views is to some extent explained by differences in beliefs and basic cooperation preferences.
Keywords: C90; D03; H41; 330; Cooperation; Social Dilemma; Political Ideology; Experiment; Simulation